2019
DOI: 10.1063/1.5080134
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of high frequency Fe-Si-Cr material for motor application by selective laser melting

Abstract: In this paper, a soft magnetic composite (SMC) material, FeSiCr, is analyzed for its beneficial electromagnetic properties and unique 3D formation capacity, which endows a very high potential to become the material for electric motor fabrication by 3D printing technology adopting high temperature selective laser melting (SLM) process. A microscopic and spectroscopic experiment performed on FeSiCr after SLM process showed that FeO is the oxide layer responsible for the unique advantages of this material. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The powder's chemical composition and particle-size distribution are listed in Table 1. The soft magnetic composite FeSiCr material is analyzed for its beneficial electromagnetic properties and unique 3D formation capacity [24]. A microscopic and spectroscopic experiment performed on FeSiCr after SLM process showed that FeO is the oxide layer responsible for the unique advantages of this material.…”
Section: Methodsmentioning
confidence: 99%
“…The powder's chemical composition and particle-size distribution are listed in Table 1. The soft magnetic composite FeSiCr material is analyzed for its beneficial electromagnetic properties and unique 3D formation capacity [24]. A microscopic and spectroscopic experiment performed on FeSiCr after SLM process showed that FeO is the oxide layer responsible for the unique advantages of this material.…”
Section: Methodsmentioning
confidence: 99%